2014
DOI: 10.1094/pdis-06-14-0580-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Wilt of Eucalyptus Caused by Ceratocystis fimbriata in China

Abstract: Eucalyptus spp., most of which are native to Australia, are one of the world's most commonly planted forestry crops, and have been widely planted in the tropics and subtropics. Eucalyptus trees are distributed in more than 600 counties in 19 provinces/regions throughout China, especially in the southern regions of the country (1). From April of 2013 to May of 2014, eucalyptus trees were noted to be wilting and dying rapidly in Kunming, Yunnan Province (25°02′ N, 102°42′ E), southwest China. Symptomatic trees t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…There are only six previous reports of Ceratocystis species from China and all species reside in the South American Clade. These species include C. manginecans from recently harvested stumps of Eucalyptus in GuangDong Province (Chen et al 2013;Fourie et al 2015), and C. fimbriata s.l, causing a disease on Eucalyptus (Li et al 2014b), Ipomoea batatas (sweet potato; Sy 1956), Punica granatum (pomegranate; Huang et al 2003;Xu et al 2011), Colocasia esculenta (taro; Huang et al 2008) and Eriobotrya japonica (loquat; Li et al 2014a). Considering the number of Ceratocystis species found in other countries, and the small number of studies on species of Ceratocystis and other Ceratocystidaceae found in China, the discovery of C. cercfabiensis and C. collisensis suggests that many other species in the genus and family remain to be discovered in this geographic area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are only six previous reports of Ceratocystis species from China and all species reside in the South American Clade. These species include C. manginecans from recently harvested stumps of Eucalyptus in GuangDong Province (Chen et al 2013;Fourie et al 2015), and C. fimbriata s.l, causing a disease on Eucalyptus (Li et al 2014b), Ipomoea batatas (sweet potato; Sy 1956), Punica granatum (pomegranate; Huang et al 2003;Xu et al 2011), Colocasia esculenta (taro; Huang et al 2008) and Eriobotrya japonica (loquat; Li et al 2014a). Considering the number of Ceratocystis species found in other countries, and the small number of studies on species of Ceratocystis and other Ceratocystidaceae found in China, the discovery of C. cercfabiensis and C. collisensis suggests that many other species in the genus and family remain to be discovered in this geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…The recent description of a disease of Eucalyptus in China, caused by C. fimbriata s.l. (Li et al 2014b), and reports of disease and death of Eucalyptus species caused by species of Ceratocystis in Africa (Roux et al 1999(Roux et al , 2000 and South America (Barnes et al 2003;Rodas et al 2008;Van Wyk et al 2012), however, suggest that these fungi could become important to Eucalyptus forestry in China. They clearly deserve further study in the future.…”
Section: Ceratocystis Cercfabiensis Was Found At All Eucalyptus Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, isolates of Ceratocystis from Eriobotrya japonica (loquat; E2‐2) and Eucalyptus (PY1‐1, PY2‐1) have been reported from YunNan Province in China and broadly treated as C. fimbriata s.l . (Li et al ., ,b). However, the ITS sequences of the latter isolates have 99% similarity to those of C. uchidae , a newly described species in the AAC group (Li et al ., ) and 100% similarity to those of the undescribed Ceratocystis sp.…”
Section: Introductionmentioning
confidence: 99%